A Programação como ferramenta didático-pedagógica para o ensino de Geometria na Educação Básica em um ambiente construcionista - Moraes, Fabio Atila Cardoso (2020)
Exploratory Descriptive research, whose research subjects are 17 students from the ninth grade of elementary school, having as field of study a state school located in the city of São Mateus. Deals with a didactic experience that contemplates the five dim